LEXICAL DISTINCTIONS BETWEEN MALANG AND MADIUN DIALECTS SPOKEN BY STUDENTS OF FACULTY OF CULTURAL STUDIES OF UNIVERSITAS BRAWIJAYA - MUSTIKA, PRISTA GIRI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Javanese Language, Javanese Dialect, Dialect Distinctions, Lexical Distinctions, Malang and Madiun Dialects, Non-linguistic and Linguistic Factors. Javanese is the language of Javanese people from the central and eastern parts of the island of Java in Indonesia. Javanese language belongs to a large number of speakers spreading widely. Therefore, it shows the variation of the Javanese language usage, which is commonly called dialects. The writer focuses on Malang and Madiun dialects. There are two problems to be solved in the study, namely: (1) what are lexical distinctions of Javanese dialects in Malang and Madiun spoken by students (2010) of Faculty of Cultural Studies of Universitas Brawijaya and (2) what are factors facilitating the lexical distinctions between Malang and Madiun dialects.This study uses descriptive qualitative approach because the aim of this study is to describe the lexical distinctions of Javanese dialect spoken by Malang and Madiun in students’ school year 2010 of Faculty of Cultural Studies in Universitas Brawijaya.The study reveals that forty one lexicons are included to onomasiology distinction, three lexicons found which are included to semasiology distinction and forty one lexicons which are included to the semantic distinction. After differentiating lexicons through three analyses, the writer obtained the factors that influence the using of lexicons of Malang and Madiun dialects. Those distinctions are facilitated by linguistic factor which are influenced by the use of vocabulary also intonation; and non-linguistic factors which are influenced by the use of behaviour and geographical area.The writer hopes that this research can contribute a better and deeper understanding especially the dialects in Javanese society. She suggests further researchers conduct a similar research in sociolinguistics, especially dialects in different distinction, such as in the terms of phonological and morphological distinction. Further researchers should use another theory to make their research more interesting and find the unique of dialects differences in different object and areas or cases.